Use Of Intra Uterine Device Contraception In Women Of Fertile Age - Wijayanti, Lumastari Ajeng; Treasa, Adisty Dwi; Wahyuni, Sri; Afritayeni, Afritayeni; Handayani, Sri; Surtikanti, Surtikanti; Hikmah, Mutiara (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Postpartum mothers are one of the targets in the family planning program because women often experience unplanned pregnancies during breastfeeding with a close gap with previous pregnancies. The purpose of the study was to determine the relationship between contraceptive use. This research method is an analytical survey research. The research method used is Analytical Observational Research, namely where the researcher only makes observations or observes the research subjects and looks for data related to the research without providing intervention on the variables to be studied. The results of the study that the Independent Variables are knowledge, age, family planning services, Husband Participation and the dependent variable is Intra Uterine Device Contraception. The results of the Chi-Square statistical test with a confidence level of ρ <α (0.05) are knowledge (ρ = 0.023), Age (ρ = 0.025), family planning services (ρ = 0.017), and husband participation (ρ = 0.043). The conclusion is that the level of knowledge, age, family planning services, and husband participation have a significant relationship with the use of contraception.